O processo de ensino-aprendizagem de estudante surdo frente aos desafios da pandemia da Covid-19. - Souza, Aldenora Fonseca de (Brasil, 2021)
Given the social isolation caused by the current situation of the Covi-19 pandemic, this research has as its main objective to describe the teaching-learning process of deaf students in regular education facing the challenges of the Covid-19 pandemic in the municipality of Parintins. From this, we sought to identify the possible challenges faced by professionals (professors and interpreters) in relation to the teaching-learning of deaf students during remote education, as well as to describe which technological resources, didactic and methodological strategies were used by these professionals. process during this period. The choice to research the topic arose in view of the difficulties faced as a listening academic during remote learning. For the development of this, we sought through qualitative research that was subdivided into: survey of schools with deaf student enrollment, definition of subjects, bibliographic survey of authors such as: Skliar (1998); Almeida (2015); Garcia (2015); Amoêdo (2017); Teixeira (2021) among others, describe about this process in the context of Covid-19. As a data collection instrument, a semi-structured interview was used with two teachers and an interpreter from a state public school of regular education located in the urban area of the city of Parintins/AM. The results obtained showed that during the period of remote education, the deaf student experienced in the strict sense of the word, the true social isolation for not having access to their mother tongue. Thus, for the teaching-learning of people with deafness to advance, it is necessary to rethink pedagogical practices that effectively promote the inclusion of these students in regular education.